Pengaruh manajemen evaluasi manajemen pendidikan teknologi terhadap kualitas lulusan teknik elektronika FT UNP - Herayono, Andhika; Giatman, Muhammad; Ernawati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The current era of globalization demands that education goes hand in hand with technological developments. Technology education evaluation management will greatly determine the quality of graduates from an educational institution. It is a special task for educational institutions to collaborate and harmonize education with technological developments. Educational institutions need to carry out evaluation management of technology education so that graduates are able to survive in the midst of labor market competition. Electronic Engineering FT UNP always conducts technology education evaluation management in order to be able to achieve the department's vision and mission. This study involved graduates of Electronic Engineering, Faculty of Engineering, University of Indonesia by utilizing a qualitative descriptive method combined with direct field observation data collection techniques and interviewing graduates regarding the achievements obtained when they completed their education. The purpose of this study is to identify and analyze the quality of graduates with the performance management evaluation of technology education which is carried out by the department on a regular basis. The results of this study indicate that the FT UNP Electronic Engineering has succeeded in producing competent and competitive graduates.